Flexural Strengthening of Prestressed Girders with Partially Damaged Strands Using Enhancement of Carbon Fiber Laminates by End Sheet Anchorages - Abbas, H. Q.; Al‐Zuhairi, A. H. (Engineering, Technology & Applied Science Research, 2022)
This paper examines the impact of flexural strengthening on the percentage of damaged strands in internally unbonded tendons in partially prestressed concrete beams (0, 14.28%, and 28.57%) and the recovering conditions using CFRP composite longitudinal laminates at the soffit, and end anchorage U-wrap sheets to restore the original flexural capacity and mitigate the delamination of the soffit of longitudinal Carbon Fiber Reinforced Polymer (CFRP) laminates. The composition of the laminates and anchors affected the stress of the CFRP, the failure mode, and thus the behavior of the beam. The experimental results revealed that the usage of CFRP laminates has a considerable impact on strand strain, particularly when anchors are employed. The EB-CFRP laminates increased the flexural capacity by approximately 13%, which corresponds to strand damage of 14.28%, while flexural capacity increased by 9.3%, strand damage increased by 28.57% for members strengthened with laminates only, and around 21.58% and 16.85% for members reinforced with laminates and end anchorings. Quasi-experimental equations have been proposed to estimate the actual stress of untethered tendons considering the effect of CFRP laminates and final fixation winding.